1998
DOI: 10.1111/j.1755-618x.1998.tb00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Insiders and Outsiders: Women's Movements and Organizational Effectiveness*

Abstract: L'efficacité organisationnelle des mouvements de la femme au Canada et en Finlande est explorée, en mettant l'accent sur l'élaboration de politiques sur la garde des enfants (1960–1990) et en tenant compte des contraintes structurelles qui sont particu‐lieres a chaque pays. Les résultats de l'efficacité des organismes féministes et axés sur la femme sont etudiés sur trois plans (programmes, mobilisation et culture). Les organismes feminins de Finlande ont été plus efficaces sur les trois plans, tandis que les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Regular annual funding of SIGs was subsequently negotiated and agreed. In bringing outsider perspectives to ISBE we are mindful that it can be difficult for insiders and outsiders to create ‘mutual understanding and alliances’ (Tyyskä, , p. 403). However, since that early clash, we now find a willingness to engage and collaborate.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Regular annual funding of SIGs was subsequently negotiated and agreed. In bringing outsider perspectives to ISBE we are mindful that it can be difficult for insiders and outsiders to create ‘mutual understanding and alliances’ (Tyyskä, , p. 403). However, since that early clash, we now find a willingness to engage and collaborate.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Tyyska's (1998) focus on Finland, as well as Ball and Charles' (2006) on Wales, found that female political insiders (whether through direct participation or powerful blocs in national politics) created new opportunities for activists to influence childcare policy change. In Sweden and West Germany, Naumann (2005) showed that public childcare mobilization is affected by differences in the political opportunities under which feminists develop their claims and in their collective identity formation as a feminist organization.…”
Section: Theoretical Orientation and Literature Reviewmentioning
confidence: 98%
“…Second, the CCCF has always had paid staff, though they experienced defunding and downsizing following the election of the Conservative government in 2006 . Finally, as a result of its governance structure, membership base and the increasing constraints of charitable status, the CCCF has adopted an 'insider' (Briskin and Eliasson 1993;Tyyska 1998) approach to working with government, keeping its public position neutral and strictly non-partisan. In contrast, members of the CCAAC (which have not registered charity status) is governed by a board of directors with elected representatives from provincial and territorial grassroots childcare SMOs.…”
Section: The Childcare Movement Landscape In Canadamentioning
confidence: 99%
“…In others, they encompass both feminist organizations and non-feminist organizations (e.g. Tyyska, 1998;Bordt, 1997). Some researchers include only "separatist" organizations such as radical feminist groups in this category (e.g.…”
mentioning
confidence: 99%